ANALISIS KOMPETENSI PRODUK UNGGULAN DAERAH PADA BATIK TULIS DAN CAP SOLO DI DATI II KOTA SURAKARTA - Soebagiyo, Daryono; Wahyudi, M. (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2008)
This research concerning local prominent product competency of âbatik tulisâ and âbatik capâ in Surakarta. Two kinds of these batik are production of small and middle scale industry (IKM Batik) where IKM Batik has became one of economy prime acti-vator in Surakarta. In this research, writers apply research methods as follows: Bayes approach technique for getting priority prominent product rank, Analytical Hierarchy Process (AHP) by using Expert Choice Software, with aim to know prominent competency of IKM in Surakarta, and Value Chain Economic Analysis started with chain mapping to priority prominent product which appertained as main rank. Research result indicates that competency approach in local industrial devel-opment relevant enough for increasing local competitiveness and finally increasing national competitiveness. It can be happened considering that competency approach try to exploit local excess and excellence uniquely.